Synthesis of Some Newer Polyhydrazides Containing Hydrazinophosphite Linkage - Shukla, J.S.; G.H. Zaidi, Mohd. (Asian Journal of Chemistry, 2010)
The polyhydrazides having inherent viscosity in the range of 0.18- 0.47 dL g–1 were prepared by polymerizing a series of diacid chloride with phospbonichydrazide in N,N´-dimethylacetamide. Oxidative thermogravimetric analysis shows that these polymers decomposed in the range of 500–720ºC. Their melting points and glass transition temperatures were evaluated from differential thermal analysis.